Synthesis, fabrication and characterization of poly nanofibers and investigation of their adsorption properties - Shooto, Ntaote David (Vaal University of Technology, 2017)
A major challenge for this generation is cleaning up heavy metal pollution disposed during industrial, domestic and agricultural activities. So, to obtain clean water resources, new treatment technologies are needed that can be applied to a broad range of highly toxic heavy metals in water. In this study, metal organic frameworks (MOFs) were synthesized from 1,2,4,5-tertabenzene carboxylic acid with metal salts of; cobalt, copper, iron, antimony, strontium and lanthanum through solvothermal method. The synthesized MOFs were reacted with polyvinyl alcohol (PVA) by electrospinning. To the best of our knowledge it is for the first time that such hybrid materials are synthesized and reported. PVA/MOF materials were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and thermogravimetry analyzer (TGA). The SEM micrographs of PVA/MOFs materials showed relatively uniform nanofibers that were non-beaded and entangled. Some formed patches, while others were partially cross linked. TGA analysis revealed that PVA/MOF nanofibers exhibited higher decomposition temperature than PVA nanofibres. Thus, it confirmed the interactive force between MOF and PVA nanofibres. FTIR plots also exhibited shifts in critical functional group positions, thus it confirmed that there was a given amount of MOFs embedded in the electrospun fibrous mat. PVA/MOFs materials were used in the adsorption of lead ions in solution to study the effects of temperature, time dependant studies and concentrations. The batch adsorption experiments were performed at five different Pb(II) ion concentrations (20, 40, 60, 80 and 100 mg/L), four different temperatures (25, 40, 60 and 80 oC), time dependent studies ranged from (5, 10, 30 and 60 min) and pH of all Pb(II) solutions were recorded to be 5.05. The results indicated that the uptake performance of PVA and PVA/MOFs nanofibers significantly changed with concentration, temperature and time. The PVA/MOFs nanofiber hybrids demonstrated greater adsorption percentage and adsorption capacity for Pb(II) ions than PVA nanofibers. PVA nanofibers showed moderate adsorption percentage and capacity performance of 25.5 % and 44.13 mg/g (meaning 44.13 mg of Pb(II) per gram of PVA nanofibers) while PVA/MOFs nanofibers showed improved percentage and capacity perfomance (PVA/Cu-MOFs 76.36 % and 152.72 mg/g), (PVA/Co-MOFs 59.41 % and 99.28 mg/g), (PVA/La-MOFs 92.27 % and 184.03 mg/g), (PVA/Cd-MOFs 83.19 % and 165.94 mg/g), (PVA/Sb-MOFs 50.66 % - 91.57 mg/g), (PVA/Sr-MOFs 58.85 % - 124.82 mg/g) and (PVA/Fe-MOFs 56.76 % - 108.82 mg/g). The adsorption data of Pb(II) ions on PVA and all PVA/MOFs nanofibers showed that a pseudo-second order kinetic model was more suitable than a pseudo first order kinetic model. The adsorption rate was much faster on PVA/MOFs nanofibers. This is marked by lower activation energy compared to PVA nanofibers activation energy. The Temkin model did not correlate well with all the adsorption data. On the contrary, Freundlich and Langmuir isotherm models described the adsorption data adequately. All PVA/MOFs nanofibers followed Langmuir isotherm model, only PVA nanofibers followed Freundlich isotherm model. The PVA and PVA/MOFs nanofibers gave negative values of enthalpy change (ΔHo) and negative values of Gibbs free energy change (ΔGo) showing the adsorption processes were exothermic and spontaneous. Moreover, obtained positive entropy changes (ΔSo) on PVA, PVA/Fe-MOF, PVA/Cu-MOF, PVA/Co-MOF and PVA/Sb-MOF nanofibers showed that the sorped Pb(II) ions were not restricted on the electrospun nanofibres and physisorption mechanism was dominant, while negative entropy changes (ΔSo) on PVA/Sr-MOF and PVA/La-MOF nanofibers indicated that chemisorption was more dominant. The influence of ubiquitous cations such as Ca(II) and Mg(II) on the adsorption of Pb(II) ions onto PVA and PVA/MOF nanofibers was also assessed. The results showed that the ubiquitous ions had no significant influence on the sorption of Pb(II) ions. Current investigation provides a method to develop novel PVA/MOFs nanofibers hybrid adsorbents for water purification system. The adsorption capacities and removal achieved with the PVA/MOFs nanofibers sorbent were higher than those for PVA sorbent. The electro spun nanofiber sorbents presents an efficient alternative for pre-treating lead ions in aqueous solutions. Results from this research demonstrated that higher performance novel nanofibers, which possessed higher adsorption percentages and capacity capabilities were obtsained far exceeding some of the commonly used adsorbents, were obtained.
Ph. D. (Partial Fulfillment) (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Nanofibers; Thermodynamics; Adsorption; Kinetics; Equilibrium; Lead; Metal-organic frameworks; Dissertations, Academic -- South Africa.; Thermodynamics.; Organometallic chemistry.; Nanostructured materials.; Adsorption.